Analisis Penentuan Rute Terbaik Menggunakan Shortest Route Problem dengan Metode UNSY untuk Meminimalisir Biaya Transportasi - Hamada, Aulia; Muryastuti, Karina; Hartono, Yudi; -, Yuniaristanto (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2016)
Printpro is printing industry. Printpro is located at Kauman, Surakarta. Printpro produces some products such as invitation cards, calenders, and hardcovers. It makes every costomers in Printpro are new costomers. The new customers’ address which is never known before makes the shipping process become a problem because the sender should find the shortest route to decrees the fuel cost. The purpose of this paper is to decide the shortest route to make the shipping process from Karanganyar to Sukoharjo easier. The decission in finding the shortest route used Shortest Route Problem approach with Unsy methode. The sortest way to get to Karanganyar was 16,6 km and to Sukoharjo was 16,2 km. With using this shortest route method for the shipping to Karanganyar dan Sukoharjo is done in September 2015 and known that the different cost of the transportation was Rp 13.560,00. It means that the transportation cost can be minimized by deciding some route.